23 W. Clark, State Records of North Carolina 63 (1904) - (:unkn) unknown (My University, 1715)
Ch. 46, An Act Concerning Servants & Slaves: Directed "that every Christian Servant shall be allowed by their Master or Mistress at the expitation of his or her time of srvice Three Barrells of Indyan Corn & two new Suits of Apparrel of the Value of Five ounds at leasr or in liey of one suit of Apparrel a good well-fixed Gun, if he bwe a Manservant."
Keywords: GUARANTEED RIGHT